The leadership challenges of wicked problems - Grint, Keith (Henry Stewart Talks, 2010)
The Leadership Challenge of Wicked Problems, The problem of change, What kind of problem are you facing: Tame, Wicked or Critical?, Elegant solutions to Tame & Critical Problems, Why Elegant Solutions don't resolve, Wicked Problems, Why Clumsy Solutions to Wicked Problems might work